The Fearful Ethical Subject: On the Fear for the Other, Moral Education, and Levinas in the Pandemic - Yan, Sijin; Slattery, Patrick (Studies in philosophy and education, 2021)
The article seeks to reclaim a type of fear lost in silent omission in education, yet central to the development of an ethical subject. It distinguishes the fear described by Martin Heidegger through the concept of befindlichkeit and fear for the other as an essential moment for ethics articulated by Emmanuel Levinas. It argues that the latter conception of fear has inverted the traditional assumption of the ideal ethical subject as fearless. It then examines how Levinas’s interpretation of fear might contribute to the discussion on fear and responsibility in the context of the COVID-19 pandemic. It concludes that fear for the other reveals our tremendous capacity to suffer for the other, which is an aspect of the emotional life that has not been identified in the general educational discourse. This inattention manifests itself as a categorical omission in which the existence of fear for the other is not recognized and impedes the ability of educators to address ethics as it is deeply lived.